PERENCANAAN JALUR INTERPRETASI WISATA KULINER BAKSO KHAS KOTA MALANG BERBASIS APLIKASI ANDROID - Jofin, Alexandria Marlinda; Moligay, Mutiara Putri; Bani, Natalia; Budiyono, Debora (BUANA SAINS, 2023)
Malang City is an area that has a lot of culinary potential. One of the culinary potentials is meatballs which are the prima donna of typical culinary dishes when visiting Malang City which can support the tourism sector. The problem is the limited information on the existence of original, delicious, healthy, and safe or halal meatball sales locations for tourism visitors. Therefore, meatball culinary does not have a location description that makes it easier for tourists to find a typical meatball culinary tourist location in Malang City. The research objectives are (1) Identifying and analyzing the potential of culinary meatball tourism typical of Malang City and (2) Developing an interpretation path plan for culinary meatball tourism typical of Malang City based on android applications. The research method used is descriptive quantitative. Based on the results of the perception and preference analysis conducted, it shows that there are 10 locations of typical meatballs in Malang City that have the potential to be developed as culinary tourism in Malang City, namely Bakso Kota Cak Man is the most preferred meatball by connoisseurs of typical meatballs in Malang City, followed by Bakso Prima Cak Herman, Bakso Cak Toha, Bakso Damas, Bakso President, Bakso Gun, Bakso Pahlawan Trip, Bakso Bakar Trowulan, Bakso Priangan Mang Yayat, and Bakso Gong.